Metabolomics Study of the Biochemical Changes in the Plasma of Myocardial Infarction Patients - Zhu, Mingdan; Han, Yanqi; Zhang, Yu; Zhang, Shaoqiang; Wei, Congcong; Cong, Zidong; Du, Wuxun (Frontiers in Physiology, 2018)
Myocardial infarction (MI) is a common and multifactorial disease that has the highest morbidity and mortality in the world. Although a number of physiological, pathological, and functional parameters have been investigated, only scarce information regarding the changes of small metabolites in the plasma has been reported, and this lack of information may cause poor MI diagnosis and treatment. In the present study, we aimed to investigate the metabolic proﬁles of plasma samples from MI patients to identify potential disease biomarkers and to study the pathology of MI. Metabolic proﬁles of the plasma of thirty MI patients and thirty controls were obtained using ultra-performance liquid chromatography/electrospray ionization quadruple time-of-ﬂight mass spectrometry (UPLC/ESI-Q-TOF/MS). The resulting data were processed using pattern recognition approaches, including principal component analysis (PCA) and partial least squares-discriminant analysis (PLS-DA), to identify the metabolites that differed between the groups. Signiﬁcant differences in the plasma levels of the following ten metabolites were observed in the MI patients compared with the controls: phosphatidylserine, C16-sphingosine, N-methyl arachidonic amide, N-(2-methoxyethyl) arachidonic amide, linoleamidoglycerophosphate choline, lyso-PC (C18:2), lyso-PC (C16:0), lyso-PC (C18:1), arachidonic acid, and linoleic acid. The changes in these ten biomarkers indicated perturbations of energy metabolism, phospholipid metabolism and fatty acid metabolism in the MI patients. These findings hold promise to advance the treatment, diagnosis and prevention of MI.